Toxicity of Five Insecticides to Culicoides Kieffer （ Diptera： Ceratopogonidae） - Chen Min Wang Feipeng Huang Xiangzhu Huang Enjiong (Plant Diseases and Pests(植物病虫害研究：英文版), 2017)
Field-collected Culicoides oxystoma adults were exposed to different concentrations of commercial insecticides including chlorpyrifos, DDVP, deltamethyrin, beta-cypermethrin and beta--cypermethrin · emamectin benzoate via filter paper method, to determine toxicity of different insecticides on C. oxystoma. Results showed that toxicities varied significantly among insecticides. Biting midges were the most susceptible to deltamethyrin （0. 060 mg/L）, followed by chlorpyrifos （0. 588 mg/L）, beta-cypermethrin （ 1. 741 rag/L）, beta-cypermethrin · emamectin benzoate （99.670 mg/L）, and DDVP （600. 496 mg/L）. After exposed to insecticides for 1 h, tested midges were transferred to recovery chamber and observed for another 24 h ; increased mortality within this period was different under different concentrations of each insecticide. Relative toxicity index of dehamethrin was maximal when used as the standard reagent.